Chelation-assisted and steric-controlled selectivity in the Pd-catalyzed C-H/C-H oxidative coupling of indoles - Vijaykumar, Muniyappa; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Chemical Communications, 2024)
We report the first regioselective C2-C7 oxidative coupling of indoles using a palladium catalyst upon the strategic installation of N-pyridinyl and C3-carbonyl, which delivers 2,7-biindoles with a broad scope (25 examples; up to 93% yield). Isolation of the catalytic intermediate reveals the initial activation of the C(7)-H bond, followed by the C(2)-H bond in indoles, and the reaction proceeds via a Pd(ii)/Pd(0) pathway. This manuscript describes the first regioselective C2-C7 oxidative coupling of indoles using a palladium catalyst through the strategic installation of N-pyridinyl and C3-carbonyl, which delivers diverse biorelevant 2-7-biindoles.